Dynamic characteristics of adsorbed monolayers of 1-dodecanethiol on gold (111) terraces from in-situ scanning tunneling microscopy imaging - Terán Arce, Fernando (1998)
The dynamics of 1-dodecanethiol self-assembled monolayers (SAMs) on Au(111) produced by contacting pure thiol was followed by in situ STM at 298 K. Initially, these SAMs constituted a heterogeneous surface consisting of disordered and ordered adsorbate domains at terraces, step edges and pits, forming a p(6 x 1) superlattice which later changed to the (√3 x √3)R30° structure. Subsequently, the c(4 x 2) superlattice was also observed. Surface dynamics involves the coalescence and Ostwald ripening phenomena at pits occurring simultaneously with adsorbate ordering at different surface domains. The difference in surface mobility between adsorbate-free and 1- dodecanethiol-covered Au(111) can be explained taking into account both gold lattice relaxation due to adsorption and alkyl chain interaction at SAM. Data analysis in terms of clustering theory allowed us to conclude that a single mechanism is likely involved in the overall surface phenomena in which the mass transport is either a nonsteady state surface diffusion or an interface transfer along step edges as rate-determining step.